Development of Reading Materials Environment-Based in VII Grade Students of Junior High School (SMPN) 1 Kuala, Indonesia - Abram Thiofilus Sitepu; Mutsyuhito Solin; Arif Rahman (BIRCU, 2019)
This study aims is to find out the development of reading material by using environment base in Junior High School (SMPN) 1 Kuala. The research study used quantitative method by using sample in VII grade student Data with total 160 students from 5 clasess. The result show multiple intelligences based writing modules is more effective in improving student learning outcomes, this is indicated by the learning outcomes of students who are taught to use a module developed which is higher by 2460 with an average of 76.75% compared to the average value of students using 2220 textbooks. an average of 69.12%.